Development and Improvement of Antiseptic Liquid Soap Production with the Addition of Gambir Extract in CV. Novalindo, Padang - Daimon Syukri (Fakultas MIPA Universitas Negeri Padang, 2022)
This activity was carried out in order to increase the effectiveness of antiseptic liquid soap by adding extracts of natural ingredients, namely catechins from Gambir so that the production of antiseptic liquid soap can be increased with the cooperation of CV Novalindo. Antiseptic liquid soap product with the addition of gambir extract was introduced and then production was carried out more in CV. Novalindo. The introduction of technology using active ingredients catechins in the manufacture of liquid soap can be utilized by CV. Novalindo to develop liquid soap made from active catechins as a natural antiseptic in liquid soap. It is hoped that this product will become a brand by CV Novalindo.